2010
DOI: 10.1029/2010ja015557
|View full text |Cite
|
Sign up to set email alerts
|

An olden but golden EISCAT observation of a quiet‐time ionospheric trough

Abstract: [1] Incoherent scatter measurements were carried out on 9 November 1987, showing the presence of an ionospheric trough in the F region. The experiment was made using the EISCAT UHF radar, and it consisted of an azimuthal scan with constant beam elevation and a meridional scan. Since the radar rotates with the Earth, beams with different directions from subsequent scans meet in the same MLT-CGMLat pixel in nonrotating frame. If the ionosphere is not too variable, these can be combined to give an average value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 32 publications
(80 reference statements)
1
22
0
Order By: Relevance
“…We defined a region of decreasing electron density, the minima of which were at least 20% lower than the background value; this region was then identified as the trough region. Our data confirm that a 20% decrease is sufficient to distinguish the trough events from the nontrough events; with this value we are able to detect trough events referred to in past studies [e.g., Collis and Häggström, 1988;Voiculescu et al, 2010]. Additionally, to verify this threshold, we showed that the trough characteristics detailed below (section 3) did not change upon increasing this value, i.e., that the trough characteristics could be obtained using a threshold of just 20%.…”
Section: Discussionsupporting
confidence: 87%
“…We defined a region of decreasing electron density, the minima of which were at least 20% lower than the background value; this region was then identified as the trough region. Our data confirm that a 20% decrease is sufficient to distinguish the trough events from the nontrough events; with this value we are able to detect trough events referred to in past studies [e.g., Collis and Häggström, 1988;Voiculescu et al, 2010]. Additionally, to verify this threshold, we showed that the trough characteristics detailed below (section 3) did not change upon increasing this value, i.e., that the trough characteristics could be obtained using a threshold of just 20%.…”
Section: Discussionsupporting
confidence: 87%
“…One mechanism for trough formation in the premidnight sector, confirmed by numerous studies, is the stagnation mechanism: eastward corotation cancels the westward convection, plasma stagnates in the nonilluminated areas, and its density drops due to lack of solar (UV) ionization [Rodger et al, 1992;Nilsson et al, 2005;Voiculescu et al, 2010;Voiculescu and Nygrén, 2007]. However, one can safely assume that the plasma is depleted by a mechanism that acts on a continuous basis and produces a trough that is visible during some time in different locations.…”
Section: Discussionmentioning
confidence: 97%
“…The plasma decays due to lack of photoionization [Whalen, 1989;Rodger et al, 1992;Nilsson et al, 2005;Voiculescu et al, 2010;Spiro et al, 1978]. The plasma decays due to lack of photoionization [Whalen, 1989;Rodger et al, 1992;Nilsson et al, 2005;Voiculescu et al, 2010;Spiro et al, 1978].…”
Section: 1002/2016ja023360mentioning
confidence: 99%
“…Methods of observation include the following: ionospheric sounders such as the networks considered by Whalen (1987Whalen ( , 1989; incoherent scatter radar, which can reveal the latitudinal structure of the trough and associated ionization temperature characteristics (Voiculescu et al, 2010); satellite TEC observations, for example by the Navy Ionospheric Monitoring System, NIMS (Kersley et al, 2004); and ionospheric tomography reconstruction using NIMS TEC observations . In more recent years TEC measurements using GPS radio transmissions have been used to observe and study the trough, for example Krankowski et al (2009) who used GPS observations from a network of receiving stations in Europe.…”
Section: Introductionmentioning
confidence: 99%